Improving the Efficiency of the Polycrystalline silicon cell using linear focus fresnel lens (Journal of the College of Basic Education, 2022)
In this research , one linear focus Fresnel lens made of PMMA plastic material has been used to increase the incident irradiance on one solar cell by concentrate the sun light ray on it and then to improve the cell performance. It is important to find the appropriate distance between the solar cell and Fresnel lens to reach the maximum power and efficiency. The distance between a solar cell with dimensions (12.5cm × 12.5cm) made of poly-crystalline Silicon and the Fresnel lens was changed. The results showed that the best distance at which the parameters ( Isc , Imp , Voc , Vmp , Pmp , FF and η ) reached their maximum values; was 55 cm. So the output power of this solar cell was (2.25watt) and efficiency (15.18%) before using Fresnel lens. The power reached the maximum value (3.23watt) at (55cm) distance and it its efficiency become (21.77%).